Interpretation of DXA densitometric and morphometric examinations - Szafrański, Tomasz; Kostyk, Tomasz; Leszczyński, Piotr (Menopause Review/Przegląd Menopauzalny, 2012)
Osteoporosis is a systemic skeletal disease characterized by low bone mass and abnormal bone microarchitecture with a consequent susceptibility to fracture. One of the most common sites of osteoporotic fractures is the spine. Osteoporotic vertebral fractures are associated with increased morbidity and mortality and they are often asymptomatic. The early detection of osteoporosis and identification of vertebral fractures are the main diagnostic objectives. Dual-energy X-ray absorptiometry (DXA) is the standard method for measurement of bone mineral density (BMD) and the only one in clinical use. Three skeletal sites for BMD measurement are the hip, lumbar spine and forearm. The measurement of BMD at the spine and hip are recommended in most of patients. The measurement of BMD at the forearm and total body bone density measurement are recommended to selected patients and is associated with some limitations. The DXA is also the main diagnostic procedure for the evaluation of osteoporosis therapy by analyzing BMD changes. Vertebral fracture assessment (VFA) seems to be a very good diagnostic tool in early detection of vertebral fractures between Th4 and L4. The Genant visual semi-quantitative method is the clinical technique of choice for diagnosing vertebral fracture with VFA. DXA and VFA are complementary tools for the diagnosis of osteoporosis, monitoring therapy and early assessment of vertebral fractures.